Pengaruh Jumlah Dewan Direksi Dan Shareholder Eqity To Total Asset Ratio Terhadap Financial Distress (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2012-2015) - Michelle Kristian (Jurnal Ekonomi, 2017)
The objective of this research was to examine the directors' size and shareholder equity ratio towards financial distress. In this research, directors' size was measured by its size and shareholder equity ratio was measured by comparing shareholder equity to total assets, while financial distress was measured by Altman Z-Score Model with five ratios. The object in this research was companies that are experiencing financial distress and were listed at Indonesia Stock ExchangeÂ (IDX) for the period 2012 until 2015. The sample was selected by using the purposive sampling method and the secondary data used in this research was analyzed by using the multiple regression method. In total, there were 22 companies that fulfilled the requirements set by the researcher. The results of this research were directors' size and shareholder equity ratio simultaneously had a significant effect on financial distress. Directors' size had no positive effect on financial distress and the Shareholder equity ratio had a positive significant effect on financial distress.